Uncertainties in atmospheric dispersion modelling during nuclear accidents. (October 2020) - Sørensen, Jens Havskov; Bartnicki, Jerzy; Blixt Buhr, Anna Maria; Feddersen, Henrik; Hoe, Steen Cordt; Israelson, Carsten; Klein, Heiko; Lauritzen, Bent; Lindgren, Jonas; Schönfeldt, Fredrik; Sigg, Robert
Abstract: Predictions of the atmospheric dispersion of radionuclides accidentally released from a nuclear power plant are influenced by two large sources of uncertainty: one associated with the meteorological data employed, and one with the source term, i.e. the temporal evolution of the amount and physical and chemical properties of the release. A methodology is presented for quantitative estimation of the variability of the prediction of atmospheric dispersion resulting from both sources of uncertainty. The methodology, which allows for efficient calculation, and thus is well suited for real-time assessment, is applied to a hypothetical accidental release of radionuclides. Highlights: Nuclear emergency preparedness. Uncertainty of meteorological data and of source terms. New methodology for estimation of uncertainty of atmospheric dispersion prediction. Ensemble prediction. Efficient real-time atmospheric dispersion model calculation.